Fabrication and structural modification of graphene oxide-tetraethyl orthosilicate solution via liquid-phase pulsed laser ablation - Tham, Anne; Siah, Kai Xin; Noor, Ikhwan Mohd; Ghazali, Ifwat; Tan, Sin Tee; Tamchek, Nizam (Laser Institute of America, 2024)
Liquid-phase pulsed laser ablation (LP-PLA) is a physical deposition technique to fabricate micro- and nanoscale particles of polymer, glass, and ceramic materials. In this work, graphene oxide (GO) that was immersed in tetraethyl orthosilicate (TEOS) and ethanol was used to fabricate the graphene-silicone polymer using the LP-PLA technique. The GO-TEOS solution was ablated with different fluences of the laser. The ablated GO-TEOS solution was characterized by Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), energy dispersive x-ray, and ultraviolet-visible (UV-Vis) spectroscopy to study the graphene-silicone polymer properties. The FTIR result shows that the laser ablation has provided sufficient laser energy to create or break the chemical species of GO and TEOS compounds as observed on Si-O and C-O bonds. The Raman result shows the changes in the intensity in the D band, which suggests that the carbon atom of the GO has been functionalized with other compounds. Several large flakes were observed in the SEM images, representing the silicon polymer with the GO aggregation. The particle size in the range of 3-8 and 66-110 μm was formed due to the presence of uniformly sized nanoparticles of the GO-TEOS mixture and aggregation of the GO-TEOS nanoparticles into clusters. The zeta potential results indicated that the stability of the GO-TEOS mixture decreases after laser ablation. The UV-Vis result shows a broad absorption band with center at 492 and 532 nm with increasing absorbance at low fluence then saturated and decreased at maximum laser fluence. From the results above, several chemical interactions between GO and TEOS were observed, and the data suggested the laser fluence as the major source to cause both photothermal and photochemical reactions on the samples. In short, laser ablations provide sufficient energy to induce chemical bonding, which further allows structural modification of materials.